The Effect of Accompaniment Music on the Concentration and Learning Outcomes of Grade VIII Students in Alpha Omega Education Tutoring Center - Jonris Tampubolon; Else Frine Tamba (Journal of Classroom Action Research, 2022)
Feeling fed up and bored in learning mathematics occurs because of the imbalance between the right brain and the left brain, by forcing the brain to work very hard, can cause fatigue in the brain which results in a decrease in the concentration of students, especially mathematics. One method that can be used to increase concentration that can make the brain can relax in learning mathematics is to listen to classical music. The results of this study showed that there was a difference in the average grade of experimental classes that used accompaniment music while learning and control classes with learning without accompaniment music, obtained the average score of the experimental class posttest was 88.00 while the control class was 76.00 and the test calculation of the difference in the average score of the experimental class posttest and control classes was obtained tcount = 2.74 < ttable = 2.05, Which means that music affects concentration and improvement of student learning outcomes. Keywords: Music, Concentration, Learning Outcome